Water Quality Credit Trading: General Principles - Tatiana Borisova; Fritz Roka (EDIS)
FE824, an 8-page fact sheet by Tatiana Borisova and Fritz Roka, reviews the basic components of a water quality credit trading program and discusses opportunities and challenges associated with a water quality credit trading program design. Includes references. Published by the UF Department of Food and Resource Economics, December 2009.